Chattering Analysis of an Optimized Sliding Mode Controller for an Electro-Hydraulic Actuator System - Chong Chee Soon; Rozaimi Ghazali; Muhamad Fadli Ghani; Chai Mau Shern; Yahaya Md. Sam; Zulfatman Has (Universitas Muhammadiyah Yogyakarta, 2022)
Wear and tear are usually caused by various factors, which reduce the life span of a mechanical part. In the control engineering of an Electrohydraulic actuator system, the wear and tear can be caused by the system or the controller itself. This article examines the chattering effect that occurs during the sliding mode controller (SMC) design, and its effect on the nonlinear electrohydraulic actuator (EHA) system. To examine the chattering phenomenon, signum function is first applied on the switching function of the SMC. Then, parameters of the controller are obtained using single objective particle swarm optimization (PSO) method. These parameters are then applied to the switching function with hyperbolic tangent function. Lastly, the performance of both functions is analysed and compared based on graph and numerical data. From the output data, chattering phenomenon generated on the signum function is greatly eliminated by using hyperbolic tangent function.